2017
DOI: 10.1002/2016ja023394
|View full text |Cite
|
Sign up to set email alerts
|

Observational properties of dayside throat aurora and implications on the possible generation mechanisms

Abstract: Observational properties of throat aurora are investigated in detail by using 7 year continuous auroral observations obtained at Yellow River Station (magnetic latitude 76.24°N). From our inspection, throat aurora is often observed under the condition of stripy diffuse aurora contacting with the persistent discrete auroral oval, and the long‐period throat aurora observations generally consist of intermittent subsequences of throat aurora brightening followed by poleward moving auroral form and throat aurora di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 100 publications
1
105
1
Order By: Relevance
“…These are all comparable with the observational properties of throat aurora, because throat auroras often contain poleward moving aurora forms (PMAFs) (Chen et al, ; Han et al, ). PMAFs have been generally accepted as the ground signature of FTE (Moen et al, ) and have tendency to occur under southward IMF (Xing et al, ), whereas throat aurora show little tendency to occur during southward IMF (Han, Hietala, et al, ). All of these results provide strong evidence that throat auroras are definite ground signatures for the magnetopause transients that are all correspondent to magnetopause indentations.…”
Section: Discussionmentioning
confidence: 99%
“…These are all comparable with the observational properties of throat aurora, because throat auroras often contain poleward moving aurora forms (PMAFs) (Chen et al, ; Han et al, ). PMAFs have been generally accepted as the ground signature of FTE (Moen et al, ) and have tendency to occur under southward IMF (Xing et al, ), whereas throat aurora show little tendency to occur during southward IMF (Han, Hietala, et al, ). All of these results provide strong evidence that throat auroras are definite ground signatures for the magnetopause transients that are all correspondent to magnetopause indentations.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) They may change the shear angle between the magnetospheric and magnetosheath magnetic field The equatorward boundary of the discrete aurora oval and the throat aurora are outlined by the red and black dots. Adapted from Han et al (2017) lines, hence affecting the β-shear relation (Swisdak et al 2010) which states whether or not asymmetric reconnection is suppressed by diamagnetic drift. The change in shear can be due to the magnetic field orientation within the jets (i.e., on the magnetosheath side).…”
Section: Nature Of Jet Boundariesmentioning
confidence: 99%
“…Are there specific solar wind conditions that lead to jets that trigger reconnection, so that it could be forecasted? Possible Connection Between Jets and Dayside 'Throat Aurora' Recently, Han et al (2015Han et al ( , 2016Han et al ( , 2017 found that dayside diffuse auroras observed near magnetic local noon often show discrete north-south aligned arcs extending from low latitudes towards the equatoward edge of the main auroral oval (Fig. 42).…”
Section: Nature Of Jet Boundariesmentioning
confidence: 99%
“…In the magnetosphere, the radiation belt electron population may be modified by magnetopause shadowing (Elkington et al, 2003;Turner et al, 2012). Consequences may even be seen on the ground, in the form of increased ionospheric convection, geomagnetic field variations, and possibly "throat" aurora observations (Hietala et al, 2012;Dmitriev and Suvorova, 2012;Archer et al, 2013b;Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%